1999
DOI: 10.1002/j.2333-8504.1999.tb01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety and Test Performance: Comparing Paper‐based and Computer‐adaptive Versions of the Gre General Test

Abstract: AcknowledgmentsI'm thankful for the assistanceand advice providedby numerous people during the conduct of this study, among them were:• Rob Durso for invaluable assistance and encouragement throughout the course of the study • Ruth Yoder for assuming major administrative responsibility for a variety of aspects of the study • Laura Jerry for providing the data analyses on which the results are based• Holly Knott for her work on computerizing the anxiety inventories (although we were unfortunately unableto use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…Computer anxiety is a fear that examinee may face when doing a computer-based test because of the possible interaction that may have with the test (Brown, 2000). Powers (1999) observed a modest negative effect of computer anxiety on CBA and P&P tests of verbal, analytical and quantitative ability, and Tseng et al (1998) also found computer anxiety to be negatively associated with both CBA and P&P test performance, although it was most strongly correlated with the former. Shermis and Lombard (1998) argued that test anxiety was responsible for their findings rather than computer anxiety itself.…”
Section: )mentioning
confidence: 93%
See 1 more Smart Citation
“…Computer anxiety is a fear that examinee may face when doing a computer-based test because of the possible interaction that may have with the test (Brown, 2000). Powers (1999) observed a modest negative effect of computer anxiety on CBA and P&P tests of verbal, analytical and quantitative ability, and Tseng et al (1998) also found computer anxiety to be negatively associated with both CBA and P&P test performance, although it was most strongly correlated with the former. Shermis and Lombard (1998) argued that test anxiety was responsible for their findings rather than computer anxiety itself.…”
Section: )mentioning
confidence: 93%
“…Shermis and Lombard (1998) argued that test anxiety was responsible for their findings rather than computer anxiety itself. Powers (1999) in his study rejected this view because his data denoted that computer and test anxiety are two separate constructs. Vogel (1994) has provided something completely different because in her study she found that computer anxiety is related to scores on a computer-based but not P&P test, whereas Vispoel et al (1994) found a negative effect on performance for test but not computer anxiety.…”
Section: )mentioning
confidence: 99%
“…While computer anxiety defined as "the fear experienced when interacting with a computer or anticipating an interaction" (McDonald, 2002, 305). This computer anxiety has contended that to overlap with computer familiarity/experience (McDonald, 2002;Powers, 1999). Thus, the computer anxiety results from a lack of familiarity and experience with using computers (see, for more details, Lee, 1986;McDonald, 2002;Powers, 1999;Taylor et al, 1999).…”
Section: Computer-based Assessment and Feedbackmentioning
confidence: 99%
“…Brojna su istraživanja uticaja računarske anksioznosti na postignuće na računarski podržanim kognitivnim testovima. Neka nalaze negativnu povezanost računarske anksioznosti i postignuća (Kanfer i Heggestad, 1997, Bloom i Hautaluoma, 1990, neka nalaze takvu povezanost samo sa određenim vrstama testova (Shermis i Lombard, 1998), dok neka nalaze negativnu povezanost računarske anksioznosti sa postignućem na kognitivnim testovima bez obzira na modalitet (Powers, 1999, Tseng, Tiplady, Macleod, & Wright, 1998. Zanimljiv je rad Vogelove (1994( , prema: McDonald, 2002 koja je pronašla odnos u obliku obrnutog slova "U" između računarske anksioznosti i postignuća na računarski podržanoj formi Graduate Record Examination -GRE.…”
Section: Istraživanja Uticaja Računarske Anksioznosti Na Testiranje Runclassified